2017
DOI: 10.12740/app/76338
|View full text |Cite
|
Sign up to set email alerts
|

Body image in women practicing yoga or other forms of fitness

Abstract: SummaryAim of the study: The aim of the study was to compare the body image of women practicing yoga and other forms of fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Self-objectification was lower in yoga practitioners in the studies analysed [27,28]. Other studies found significant relationships between continued yoga practice and positive body image [34,54,55]. These results support the potential of yoga practice in increasing individuals' self-image and its use for the prevention of disordered eating attitudes.…”
Section: Eating Behaviours and Correlates In Yoga Practitionersmentioning
confidence: 51%
“…Self-objectification was lower in yoga practitioners in the studies analysed [27,28]. Other studies found significant relationships between continued yoga practice and positive body image [34,54,55]. These results support the potential of yoga practice in increasing individuals' self-image and its use for the prevention of disordered eating attitudes.…”
Section: Eating Behaviours and Correlates In Yoga Practitionersmentioning
confidence: 51%
“…The most direct activity with which the body is involved is exercise. During exercise, the individual improves this perception and belief about their body, enhancing their emotional relationship with the body through this specific behavior [12]; thereby improving one's sense of competence, belief in their body, and increasing one's sense of self-efficacy. Recent studies have found a close relationship between self-efficacy and depression in Chinese college students, and that self-efficacy can negatively predict their depression [13].…”
Section: Introductionmentioning
confidence: 99%
“…Сучасна фітнес індустрія пропонує безліч фізкультурно-оздоровчих систем [2,3,4,5,8]. Проте методика занять фізичними вправами з жінками 45-50 років потребує особливого підходу, оскільки для жінок даного віку характерно зниження показників фізичних якостей, наявність соматичних захворювань та функціональних розладів систем організму [1,6,7,9,10]. Очевидна потреба в вивченні впливу різних видів фізкультурно-оздоровчих занять (ФОЗ) на психофізичний стан та рухові можливості 45-50 років [10,11,12].…”
unclassified